Development of fragility curves for confined masonry buildings in Lima, Peru - Lovon H. (2018)
The authors wish to express their gratitude to the Pontifical Catholic University of Peru (PUCP), to the National Council of Science, Technology and Technological Innovation (CONCYTEC) in the framework of the 027-2015-FONDECYT agreement, and to the Global Earthquake Model (GEM). To all these institutions for the financial aid, without this work could not have achieved. Also, the authors appreciate the support and guidance of Dr. Marcial Blondet, who provided the results of the buildings’ surveys.